Submission of contractor's all risk (CAR) insurance - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of contractor's all risk (CAR) insurance for BRACU new campus project.